2004
DOI: 10.1523/jneurosci.1220-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Hierarchical Modulation of Vocal Patterning by Steroid Hormones

Abstract: Vocal control systems have been identified in all major groups of jawed vertebrates. Although steroid hormones are instrumental in the long-term development and maintenance of neural structures underlying vocalization, it is unknown whether steroids rapidly modulate the neural activity of vocal motor systems. The midshipman fish generates advertisement and agonistic calls that mainly differ in duration. A descending midbrain pathway activates a hindbrain-spinal vocal circuit that directly establishes the disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
140
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(147 citation statements)
references
References 79 publications
(96 reference statements)
7
140
0
Order By: Relevance
“…The rapid behavioral activation observed in this experiment [64] thus potentially illustrates in males the synergistic interaction between rapid and slower genomic actions of estradiol as also demonstrated by recent work on female rats (see work of Kow and Pfaff and Vasudevan et al described above; [138,266]). In plain midshipman fish, an intramuscular injection of E 2 increases within 5 min the duration of fictive vocalizations stimulated by electrical stimuli in an in vitro preparation [208]. This effect persists for 15 to 30 min.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The rapid behavioral activation observed in this experiment [64] thus potentially illustrates in males the synergistic interaction between rapid and slower genomic actions of estradiol as also demonstrated by recent work on female rats (see work of Kow and Pfaff and Vasudevan et al described above; [138,266]). In plain midshipman fish, an intramuscular injection of E 2 increases within 5 min the duration of fictive vocalizations stimulated by electrical stimuli in an in vitro preparation [208]. This effect persists for 15 to 30 min.…”
Section: Introductionmentioning
confidence: 93%
“…[218]. Remage-Healey and colleagues also recently demonstrated that 11-keto-testosterone (11kT, the main androgen in fishes) rapidly increases the duration of fictive vocalizations stimulated by electrical stimuli in an in vitro preparation ( [208], Remage-Healey and Bass, 2006, cited in [206]). Finally, Clifton and Andrew (1981, [61]) also suggested the existence of rapid effects of testosterone on aggressive behavior in chicks presented with foreign objects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the plainfin midshipman, a species that also presents male alternative reproductive phenotypes, injections of both 11KT and E 2 facilitated the duration of fictive vocalizations in courting males measured in a neurophysiological brain preparation (Remage-Healey and Bass, 2004). However, the fact that courting males presented much lower levels of aromatase in brain regions implicated in the control of vocal courtship displays when compared with parasitic males and females (Schlinger et al, 1999) suggests that T conversion into E 2 is not a main mechanism facilitating male vocal courtship behavior in this species.…”
Section: Differences Between Populationsmentioning
confidence: 99%
“…Also, in the goldfish testosterone (T) and estradiol (E 2 ) injections in males stimulated approach behavior toward females within minutes, while fadrozole blocked the stimulatory effect of T (Lord et al, 2009). Finally, in the plainfin midshipman intramuscular injections of both 11KT and E 2 to courting males facilitated the duration of fictive vocalizations (similar to natural vocalizations produced in an agonistic and sexual context) measured in a neurophysiological brain preparation (Remage-Healey and Bass, 2004). These examples would suggest that, similarly to what has been found for birds and mammals, E 2 locally synthesized in the brain from testosterone (T) facilitates some aspects of male sexual behavior in fishes.…”
Section: Introductionmentioning
confidence: 99%